PIONIRS: Implementation of Public Service Innovation Policy to Promote E-Government System in Pontianak City Government, West Kalimantan - Maryuni, Sri (Jurnal Manajemen Pelayanan Publik, 2024)
The Pontianak Agency of Population Administration and Civil Registry has implemented online licensing innovations in various aspects of its services to support e-government implementation, including the PIONIRS (Online Services from Home) program, which aims to simplify obtaining population documents for the people of Pontianak City.  This study employs a descriptive approach with qualitative analysis techniques to examine the implementation process of public service innovation policies through PIONIRS at the Pontianak Agency of Population Administration and Civil Registry, covering organization, interpretation, and application. The results indicate that this innovation represents a progressive step with potential for adoption by other regional entities, as evidenced by the involvement of socialization partners and the ability to accelerate public needs transition. However, the implementation process still encounters several challenges, including limited resources, the lack of standard operating procedures (SOPs) for online programs like PIONIRS, and insufficient community understanding of the service innovation policies. The integrated system aims to improve performance by prioritizing efficiency and public satisfaction through service simplification and increased online service engagement. Recommendations emphasize the importance of developing a structured system to support innovation in programming, expanding networks of partners and sectors, and implementing comprehensive affirmative education for the community through outreach.